EEG coherence as a diagnostic tool to measure the initial stages of Parkinson Disease. (February 2019) - Gongora, Mariana; Velasques, Bruna; Cagy, Mauricio; Teixeira, Silmar; Ribeiro, Pedro
Abstract: Although Parkinson Disease was described a long time ago by James Parkinson and several biomarkers were used to predict the symptoms of PD, there is no accepted tool to distinguish the initial stages of this pathology. The present hypothesis discusses the Coherence Function, an Electroencephalography measure which could be used as a simple, and low-cost tool to describe the onset of cardinal signals of PD. Our hypothesis is based on three factors: beta frequency related to movement, motor action over particular cortical regions, and cortical coupling between cortical areas involved in the execution of voluntary movement. We believe that these factors support our hypothesis pointing out coherence function as an interesting measure to detect initial stages of PD.